Three-dimensional graphene with dual atomic-level defects and preparation method and application thereof

CN119873807BActive Publication Date: 2026-10-20GUANGDONG IND TECHN COLLEGE +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411885784.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2026-10-20
Estimated Expiration
2044-12-20

AI Technical Summary

Benefits of technology

[0058](1)本发明提供了一种“双重原子级缺陷引导技术”,通过同步引入氧化还原性缺陷和结构缺陷,在三维石墨烯材料中创建一种高度可控的缺陷网络。这种技术不仅能够实现缺陷的多样性,还可以通过精确控制缺陷的分布和密度,使缺陷更均匀地分布在材料表面,提升材料的结构稳定性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119873807B_ABST
    Figure CN119873807B_ABST
Patent Text Reader

Abstract

The application discloses three-dimensional graphene with double atomic-level defects and a preparation method and application thereof. The three-dimensional graphene skeleton is grown by a high-temperature chemical vapor deposition method, and styrene and chlorine gas are introduced to control the initial morphology of the graphene. Then, precise phosphorus and nitrogen co-doping is introduced by using a low-temperature plasma-assisted chemical vapor deposition method, and the precursor is a phosphonamide compound. Further, laser irradiation annealing technology is used to optimize the defect type and distribution, form uniform redox active sites, and obtain the three-dimensional graphene nanomaterial with phosphorus and nitrogen co-doping. The electrochemical energy storage device performance of the material is excellent, and the potassium ion hybrid capacitor device capacity is high, the rate is high, and the service life is long when the material is used as a negative electrode.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of nanomaterials technology, and specifically relates to a three-dimensional graphene with dual atomic-level defects, its preparation method, and its application. Background Technology

[0002] Graphene has attracted much attention in electrochemical energy storage devices (such as supercapacitors and batteries) due to its excellent properties, including high conductivity, high specific surface area, and high mechanical strength. Introducing graphene structures can effectively improve the conductivity of electrode materials and enhance ion storage capacity, thereby increasing the power density and energy density of the devices. However, the electrochemical performance of graphene materials in practical applications still has some shortcomings. For example, its ability to store large-radius ions (such as potassium ions) is relatively low, and its structure is prone to changes during cycling, leading to capacity decay. Therefore, how to further improve the electrochemical performance of graphene materials has become a current research hotspot.

[0003] Compared to lithium-ion capacitors, potassium-ion capacitors (KICs) have attracted much attention due to their low cost, abundant potassium resources, and high energy density, particularly showing potential advantages in low-cost and large-scale energy storage. However, the radius of potassium ions... The relatively large size of potassium ions can easily lead to volume expansion and structural collapse within the material, posing challenges to the structural stability and cycle life of the electrode material. Furthermore, due to the slow diffusion rate of potassium ions, traditional electrode materials struggle to achieve efficient ion conduction, limiting the charge and discharge rates of potassium-ion capacitors. Therefore, designing novel electrode materials with high conductivity and excellent ion storage performance, particularly graphene-based electrode materials, has become crucial for solving the bottleneck problems of potassium-ion capacitors.

[0004] In the preparation of graphene materials, defects are generally considered unavoidable, and these defects significantly affect the electrochemical performance of graphene. Recent studies have shown that reasonable defect introduction and modulation techniques can alter the electronic structure and surface properties of graphene, helping to improve its electrical conductivity, specific surface area, and active site distribution, thereby enhancing its electrochemical performance. For example, doping with non-metallic elements (such as nitrogen and sulfur) or introducing microcrack structures has been proven to significantly improve the electrochemical activity of graphene. However, these traditional defect modulation methods, while improving material performance, often face problems such as poor structural stability and uneven defect distribution. Therefore, a novel defect modulation technique is urgently needed to introduce dual atomic-level defects to regulate the electrochemical performance of three-dimensional graphene, making it suitable for applications in potassium-ion hybrid capacitors. Summary of the Invention

[0005] The primary objective of this invention is to overcome the shortcomings and deficiencies of the prior art and provide a method for preparing three-dimensional graphene with dual atomic-level defects.

[0006] Another object of the present invention is to provide three-dimensional graphene with dual atomic-level defects obtained by the above preparation method.

[0007] Another object of the present invention is to provide applications of the above-mentioned three-dimensional graphene with dual atomic-level defects.

[0008] The objective of this invention is achieved through the following technical solution: a method for preparing three-dimensional graphene with dual atomic-level defects, comprising the following steps:

[0009] (1) Preparation of three-dimensional graphene material precursors

[0010] Biomass was placed in a vacuum environment as a raw material and then pretreated and carbonized under an inert atmosphere to obtain a three-dimensional graphene material precursor.

[0011] (2) Preparation of three-dimensional graphene materials

[0012] The three-dimensional graphene precursor obtained in step (1) was placed in a vacuum environment and treated by chemical vapor deposition (CVD) in a mixture of styrene and chlorine gas. Then, the three-dimensional graphene prepared by chemical vapor deposition was further treated in a low-temperature plasma environment to obtain a three-dimensional graphene sample.

[0013] (3) Preparation of three-dimensional graphene materials with dual defects

[0014] The three-dimensional graphene sample obtained in step (2) is placed in the middle of the CVD reaction chamber; liquid diethylphosphonamide is added to the evaporator of the CVD system, inert gas is introduced, the temperature of the reaction chamber is gradually increased, the system pressure is adjusted, and the reaction is carried out to obtain phosphorus and nitrogen co-doped three-dimensional graphene; then, a controllable laser system is used to irradiate the phosphorus and nitrogen co-doped three-dimensional graphene to obtain a three-dimensional graphene material with dual defects.

[0015] The biomass mentioned in step (1) is preferably plant-based biomass; more preferably, it is biomass from grasses; and most preferably, it is bamboo fiber or natural reed.

[0016] The vacuum environment described in step (1) is preferably a quartz tube that has been evacuated.

[0017] The pressure of the vacuum environment is 5 to 20 mTorr; preferably 10 mTorr.

[0018] The inert atmosphere mentioned in step (1) is preferably argon.

[0019] The flow rate of the inert atmosphere is preferably 40-80 sccm; more preferably 60 sccm.

[0020] The temperature of the pretreatment carbonization in step (1) is 400-800℃; preferably 600℃.

[0021] The pretreatment carbonization time in step (1) is preferably 0.5 to 4 hours; more preferably 2 hours.

[0022] The vacuum environment described in step (2) is preferably a quartz tube that has been evacuated.

[0023] The pressure of the vacuum environment is 5 to 20 mTorr; preferably 10 mTorr.

[0024] In step (2), the styrene is introduced into a heated vaporizer at room temperature via a gas delivery device, and the vaporizer temperature is maintained at 80°C.

[0025] In step (2), argon is used as a carrier gas to carry gaseous styrene into the CVD reaction system.

[0026] The chlorine gas mentioned in step (2) is supplied directly through a high-purity gas cylinder.

[0027] The flow rate ratio of styrene to chlorine is preferably 0.5 to 4:1; more preferably 2:1.

[0028] The flow rate of the styrene is preferably 50-100 sccm; more preferably 80 sccm.

[0029] The flow rate of the chlorine gas is preferably 20-60 sccm; more preferably 40 sccm.

[0030] The preferred heating rate for the chemical vapor deposition process in step (2) is 0.1–20 °C / min. -1 More preferably, 1–10 °C / min -1 The optimal temperature is 5℃ min. -1 .

[0031] The temperature of the chemical vapor deposition process in step (2) is preferably 100-1200℃; more preferably 400-1000℃; and most preferably 900℃.

[0032] The processing time for the chemical vapor deposition method described in step (2) is preferably 0.1 to 9 hours; more preferably 1 to 6 hours; and most preferably 3 hours.

[0033] The low-temperature plasma mentioned in step (2) is preferably prepared by a low-temperature plasma generating device, which includes a vacuum chamber, a gas supply system, a plasma excitation source, an electrode system, and a cooling system.

[0034] The preferred preparation conditions for the low-temperature plasma are as follows: cavity pressure is 10... -2 ~10 -6 The ratio of Torr, hydrogen (H2), and nitrogen (N2) is 1:3 to 1:5; the total gas flow rate is 50 to 200 sccm; the excitation frequency is 100 to 300 W; and the temperature range is 50 to 500 °C. More preferably, the chamber pressure is 10... -4 The ratio of Torr, hydrogen (H2) to nitrogen (N2) is 1:4, the total gas flow rate is 100 sccm, the excitation frequency is 200W, and the temperature range is 300℃.

[0035] The preferred inert atmosphere is argon.

[0036] The temperature for the further processing described in step (2) is preferably 50 to 500°C; more preferably 300°C.

[0037] The time for the further processing described in step (2) is preferably 0.1 to 2 hours; more preferably 1 hour.

[0038] The amount of liquid diethylphosphonamide used in step (3) is preferably calculated as 5 to 20 mL of liquid diethylphosphonamide per 100 mg of three-dimensional graphene sample; more preferably, it is calculated as 10 mL of liquid diethylphosphonamide per 100 mg of three-dimensional graphene sample.

[0039] The temperature of the evaporator in step (3) is 40 to 100°C; preferably 70°C.

[0040] The inert gas mentioned in step (3) is preferably argon.

[0041] The flow rate of the inert gas in step (3) is 0 to 50 sccm, excluding the endpoint value of 0; preferably 20 sccm.

[0042] The temperature of the reaction chamber in step (3) is 200-1000℃; preferably 600℃.

[0043] The system pressure mentioned in step (3) is 10. -1 ~10 -4 Torr; preferably 10 -2 Torr.

[0044] The reaction time described in step (3) is 0.5 to 4 hours; preferably 2 hours.

[0045] The power density of the laser irradiation in step (3) is 1–8 W / cm². 2 The preferred value is 5W / cm. 2 .

[0046] The laser irradiation time in step (3) is 5 to 20 minutes; preferably 10 minutes.

[0047] A three-dimensional graphene with dual atomic-level defect-guided modulation was obtained by the above-described preparation method. It exhibits higher energy density and power density, making it particularly suitable for high-performance energy storage devices such as potassium-ion hybrid capacitors.

[0048] The application of the aforementioned three-dimensional graphene with dual atomic-level defects in the field of electrochemical energy storage technology is particularly suitable for the preparation of potassium-ion hybrid capacitors, lithium-ion batteries, sodium-ion batteries, or supercapacitors.

[0049] A potassium-ion hybrid capacitor includes a positive electrode, a negative electrode, a separator, and an electrolyte; the negative electrode is made of the aforementioned three-dimensional graphene with dual atomic-level defects.

[0050] The positive electrode material is the three-dimensional graphene with dual atomic-level defects mentioned above, which has been thoroughly activated by KOH solution.

[0051] The preferred preparation steps for the material thoroughly activated by KOH solution are as follows: Three-dimensional graphene with dual atomic-level defects is thoroughly mixed with potassium hydroxide solution, wherein the three-dimensional graphene with dual atomic-level defects and potassium hydroxide are mixed in a mass ratio of 1:3; the mixture is heated to 800°C in an inert atmosphere at a heating rate of 5°C / min and held for 2 hours; the activated product is washed with hydrochloric acid to remove excess activator, then repeatedly rinsed with deionized water, and finally dried to obtain three-dimensional graphene with dual atomic-level defects activated by KOH.

[0052] The electrolyte is a KFSI solution with diethyl carbonate and ethylene carbonate (DEC / EC, 1:1, volume ratio) as solvents, and the concentration of KFSI is 1M.

[0053] The diaphragm is made of glass microfiber; preferably Whatman GF / F glass microfiber.

[0054] The positive and negative electrodes can be cut to appropriate sizes before assembly, preferably circular with a diameter of 14mm.

[0055] The assembly of the potassium ion mixed capacitor is completed in an argon-filled glove box, preferably with an oxygen concentration of <0.5ppm and a moisture concentration of <0.5ppm.

[0056] The potassium-ion hybrid capacitor device described above has excellent fast charge and discharge performance, making it suitable for application in the field of electrochemical energy storage technology.

[0057] The present invention has the following advantages and effects compared with the prior art:

[0058] (1) This invention provides a “dual atomic-level defect-guided technology” that creates a highly controllable defect network in three-dimensional graphene materials by simultaneously introducing redox defects and structural defects. This technology not only enables the diversity of defects, but also improves the structural stability of the material by precisely controlling the distribution and density of defects, making the defects more uniformly distributed on the material surface.

[0059] (2) The novel phosphonamide compound (diethylphosphonamide, (C2H5O)2P(O)NH2) provided by this invention is used as a phosphorus and nitrogen co-doping source. Through one-step chemical vapor deposition (CVD) combined with low-temperature plasma technology, efficient and uniform doping control is achieved. The process is simple and easy to implement, avoiding the high energy consumption and pollution problems of traditional multi-step chemical processing.

[0060] (3) Using the three-dimensional graphene nanomaterial with dual atomic level defect guidance and regulation provided by the present invention as the negative electrode, the resulting potassium ion capacitor has high capacity, high rate of return and long life. Attached Figure Description

[0061] Figure 1 The images shown are scanning electron microscope (SEM) and transmission electron microscope (TEM) images of the phosphorus-nitrogen co-doped three-dimensional graphene nanomaterials prepared in Example 1. Among them, (a) is a scanning electron microscope image of the phosphorus-nitrogen co-doped three-dimensional graphene nanomaterials with a scale bar of 2 μm; and (b) is a TEM image of the phosphorus-nitrogen co-doped three-dimensional graphene nanomaterials with a scale bar of 50 nm.

[0062] Figure 2 The Raman spectroscopy and X-ray photoelectron spectroscopy (b) results of the phosphorus-nitrogen co-doped three-dimensional graphene nanomaterials prepared in Example 1 are shown.

[0063] Figure 3 The nitrogen adsorption-desorption curves of the phosphorus and nitrogen co-doped three-dimensional graphene nanomaterials prepared in Example 1 are shown in Figure 1. (a) is the nitrogen adsorption-desorption curve of the phosphorus and nitrogen co-doped three-dimensional graphene nanomaterials, and (b) is the nitrogen adsorption-desorption curve of the three-dimensional graphene nanomaterials.

[0064] Figure 4 The electron paramagnetic resonance spectra of the three-dimensional graphene nanomaterials prepared in Example 1 and the phosphorus-nitrogen co-doped three-dimensional graphene nanomaterials are shown.

[0065] Figure 5 This is a graph showing the elemental composition of the phosphorus and nitrogen co-doped three-dimensional graphene nanomaterials prepared in Example 1.

[0066] Figure 6 This is a rate performance diagram for potassium-ion hybrid capacitors.

[0067] Figure 7 This is a diagram showing the long cycle life of the potassium ion hybrid capacitor device in Example 1. Detailed Implementation

[0068] The present invention will be further described in detail below with reference to the embodiments and accompanying drawings, but the embodiments of the present invention are not limited thereto.

[0069] Example 1

[0070] I. A method for preparing three-dimensional graphene nanomaterials guided and regulated by dual atomic-level defects:

[0071] (1) Preparation of three-dimensional graphene material precursors

[0072] Bamboo fiber was placed in a vacuum quartz tube and then pretreated and carbonized at 600°C under an argon atmosphere for 2 hours, with an argon flow rate of 60 sccm.

[0073] (2) Preparation of three-dimensional graphene materials

[0074] The three-dimensional graphene precursor obtained in step (1) is placed in a vacuum-sealed quartz tube. Styrene is introduced into the CVD reaction system at a flow rate of 80 sccm using argon as the carrier gas (the volume concentration of styrene in argon is usually set at 50%). Chlorine is introduced into the CVD reaction system at a flow rate of 40 sccm. The CVD reaction system is operated at 5℃ for 1 minute. -1 The temperature was increased at a controlled rate to 900°C. The three-dimensional graphene precursor was then subjected to CVD treatment at 900°C for 3 hours in a styrene and chlorine mixture.

[0075] Low-temperature plasma was prepared using a plasma-enhanced chemical vapor deposition system, with a cavity pressure of 10. -4 The ratio of Torr, hydrogen (H2) to nitrogen (N2) is 1:4, the total gas flow rate is 100 sccm, the excitation radio frequency is 200 W, and the temperature range is 300℃.

[0076] The three-dimensional graphene prepared by CVD was placed in a low-temperature plasma environment and continuously treated at 300°C for 1 hour to obtain a three-dimensional graphene sample.

[0077] (3) Preparation of three-dimensional graphene materials with dual defects

[0078] The 100 mg three-dimensional graphene sample obtained in step (2) was placed in the middle of the CVD reaction chamber; 10 mL of liquid diethylphosphonamide (referring to dichloroN,N-diethylphosphonamide, CAS number 1069-08-5) was added to the evaporator of the CVD system, and the temperature of the evaporator was set to 70 °C; argon gas was introduced, and the flow rate was controlled at 20 sccm; the temperature of the reaction chamber was gradually increased to 600 °C, and the system pressure was adjusted to 10⁻² Torr, and the reaction time was 2 h; the phosphorus and nitrogen co-doped three-dimensional graphene was irradiated with a controllable laser system, and the power density of the laser was controlled at 5 W / cm². 2 The irradiation time was 10 minutes, resulting in a three-dimensional graphene material with dual defects.

[0079] II. Testing

[0080] (1) Structural composition inspection

[0081] The prepared three-dimensional graphene nanomaterials with dual defects were tested by field emission scanning electron microscopy (SEM) and transmission electron microscopy (TEM), and the results are as follows: Figure 1 As shown, these nanosheets can interconnect and form a 3D carbon framework with randomly distributed pores. Figure 1 (a)); TEM images clearly show that the phosphorus-nitrogen co-doped three-dimensional graphene nanomaterials exhibit a nanosheet structure similar to silk gauze, and their surface also shows an uneven wrinkle morphology consistent with the SEM results. Figure 1 (b) in the middle.

[0082] The prepared three-dimensional graphene nanomaterials with dual defects were characterized by Raman spectroscopy and high-resolution XPS, and the results are as follows: Figure 2 As shown: (a) shows the ratio of the two peak intensities I of the phosphorus-nitrogen co-doped three-dimensional graphene nanomaterials. D / I G The value reached 1.29, indicating that the phosphorus and nitrogen co-doped three-dimensional graphene nanomaterials have very rich edges and defects in the graphite sheet plane; (b) shows that the C1s peak fits into five peaks, which correspond to the C=C bond, CO bond, CN bond, CP bond and C=C bond that occupy the main components, respectively.

[0083] The prepared three-dimensional graphene nanomaterials with dual defects were characterized by N2 adsorption-desorption analysis, and the results are as follows: Figure 3 As shown. From Figure 3 It can be seen that the specific surface area of ​​the three-dimensional graphene nanomaterial prepared in step (2) is 486.72 m². 2 g -1 The specific surface area of ​​the three-dimensional graphene nanomaterial with dual defects prepared in step (3) is 542.39 m². 2 g-1 This indicates that the specific surface area of ​​the three-dimensional graphene nanomaterials after phosphorus-nitrogen co-doping and laser irradiation treatment increased.

[0084] Electron paramagnetic resonance (EPR) spectroscopy characterization was performed on the three-dimensional graphene nanomaterial with dual defects, and the results are as follows: Figure 4 As shown, nitrogen atoms, phosphorus atoms, and defects have been successfully introduced into the surface of three-dimensional graphene nanomaterials.

[0085] The elemental composition of the three-dimensional graphene nanomaterial with dual defects was characterized, and the results are as follows: Figure 5 As shown: the nitrogen and phosphorus atoms contain 8.59 at% and 3.57 at%, respectively.

[0086] (2) Performance testing

[0087] Activation of dual-defect three-dimensional graphene nanomaterials (NP-3DPG): NP-3DPG and potassium hydroxide solution were thoroughly mixed to obtain a mixture, wherein NP-3DPG and potassium hydroxide activator were in a mass ratio of 1:3. The mixture was placed in a tube furnace and heated to 800°C at a heating rate of 5°C / min under an argon protective atmosphere, and held for 2 hours. The activated product was washed with hydrochloric acid to remove excess activator, followed by repeated rinsing with deionized water. Finally, the product was dried overnight in an oven at 60°C to obtain activated NP-3DPG, which is the cathode material ANP-3DPG.

[0088] Assembly of Potassium-Ion Hybrid Capacitors (PIHCs): A potassium-ion hybrid capacitor was constructed using NP-3DPG as the negative electrode material and KOH-activated ANP-3DPG as the positive electrode material. To optimize device performance, the mass ratio of the negative electrode to the positive electrode active material was set to 1:3.

[0089] Before assembling a complete ANP-3DPG / / NP-3DPG potassium-ion hybrid capacitor, both the negative NP-3DPG and positive ANP-3DPG electrodes require pretreatment. Under half-cell conditions, at a current density of 0.2 Ag... -1 The current density was subjected to five cycles of activation treatment, and the negative electrode material was finally potassiumized to a state of 0.01V.

[0090] The electrolyte used was 1.0M KFSI (potassium fluorosulfonamide) dissolved in a mixed solvent of EC:DEC (1:1 volume ratio). The separator was a Whatman brand GF / F glass fiber membrane. Assembly and disassembly of the potassium-ion hybrid capacitor were performed in an argon-filled glove box (the moisture and oxygen content in the glove box should be maintained below 0.1 ppm) to ensure the device was not affected by external air and moisture. The energy storage performance of the prepared potassium-ion hybrid capacitor was studied using a constant current charge-discharge test. The constant current charge-discharge test of the potassium-ion capacitor was performed at room temperature using a Shanghai Huachen CHI 760D electrochemical workstation. The test voltage window was 0-4.0V. The results are as follows: Figure 6 As shown. By Figure 6 It can be seen that the capacitance range of the potassium-ion capacitor device prepared above is from 0.05 Ag. -1 135.6mAh g -1 Change to 10Ag -1 25.83mAh g -1 This indicates that it has good rate capability.

[0091] The potassium-ion capacitor was subjected to long-cycle testing, and the results are as follows: Figure 7 As shown, this potassium-ion capacitor device is in 0.5A g -1 and 2.0A g -1 After 20,000 continuous charge-discharge cycles at the specified current density, the capacitance retention rates were 98.2% and 96.5%, respectively, indicating that the potassium-ion capacitor has excellent cycle stability.

[0092] Examples 2-5

[0093] The preparation methods of Examples 2-5 are the same as those of Example 1, except that the temperature used for precursor pretreatment in step (1) is different. The specific temperature control in the preparation methods of Examples 2-5 is shown in Table 1.

[0094] Table 1 Temperature Control of Precursor Pretreatment

[0095]

[0096] Examples 6-9

[0097] The preparation methods of Examples 6-9 are the same as those of Example 1, except that the time used for precursor pretreatment in step (1) is different. The specific temperature control in the preparation methods of Examples 6-9 is shown in Table 2.

[0098] Table 2 Time Control of Precursor Pretreatment

[0099]

[0100] Examples 10-13

[0101] The preparation methods of Examples 10-13 are the same as those of Example 1, except that the flow ratio of styrene to chlorine in the three-dimensional graphene material growth process in step (2) is different, and the total flow rate of the introduced gas is 100 sccm. The specific control of the flow ratio of styrene to chlorine in the three-dimensional graphene growth process in the preparation methods of Examples 10-13 is shown in Table 3.

[0102] Table 3. Flow ratio control of styrene and chlorine.

[0103]

[0104]

[0105] Examples 14-17

[0106] The preparation methods of Examples 14-17 are the same as those of Example 1, except that the temperature used for CVD treatment in step (2) is different. The specific temperature control in the preparation methods of Examples 14-17 is shown in Table 4.

[0107] Table 4 Temperature Control of CVD Processing

[0108]

[0109] Examples 15-18

[0110] The preparation methods of Examples 15-18 are the same as those of Example 1, except that the time used for CVD treatment in step (2) is different. The specific time control in the preparation methods of Examples 15-18 is shown in Table 5.

[0111] Table 5 Time Control of CVD Processing

[0112]

[0113] Examples 19-22

[0114] The preparation methods of Examples 19-22 are the same as those of Example 1, except that the temperature used in the plasma CVD treatment in step (2) is different. The specific temperature control in the preparation methods of Examples 19-22 is shown in Table 6.

[0115] Table 6 Temperature control of plasma CVD treatment

[0116]

[0117]

[0118] Examples 23-26

[0119] The preparation methods for Examples 23-26 are the same as those for Example 1, except that the volume of diethylphosphonamide used in step (3) is different. Specific volume control details for the preparation methods of Examples 23-26 are shown in Table 7.

[0120] Table 7 Volume control of diethylphosphonamide

[0121]

[0122] Examples 27-30

[0123] The preparation methods of Examples 27-30 are the same as those of Example 1, except for the power density of the laser in step (3). The specific power density control in the preparation methods of Examples 27-30 is shown in Table 8.

[0124] Table 8 Power density modulation of lasers

[0125]

[0126] It is evident that the potassium-ion capacitor of the present invention has the characteristics of large capacity, high rate capability, and long lifespan, and also has the advantages of high energy density, and has great application prospects in the field of electrochemical energy storage technology.

[0127] The above embodiments are preferred embodiments of the present invention, but the embodiments of the present invention are not limited to the above embodiments. Any changes, modifications, substitutions, combinations, or simplifications made without departing from the spirit and principle of the present invention shall be considered equivalent substitutions and shall be included within the protection scope of the present invention.

Claims

1. A method for preparing three-dimensional graphene with dual atomic-level defects, characterized in that... Includes the following steps: (1) Preparation of three-dimensional graphene material precursors Biomass was placed in a vacuum environment as a raw material and then pretreated and carbonized under an inert atmosphere to obtain a three-dimensional graphene material precursor. (2) Preparation of three-dimensional graphene materials The three-dimensional graphene material precursor obtained in step (1) was placed in a vacuum environment and treated by chemical vapor deposition in a mixture of styrene and chlorine gas. Then, the three-dimensional graphene prepared by chemical vapor deposition was further treated in a low-temperature plasma environment to obtain a three-dimensional graphene sample. (3) Preparation of three-dimensional graphene materials with dual defects The three-dimensional graphene sample obtained in step (2) is placed in the middle of the CVD reaction chamber; liquid diethylphosphonamide is added to the evaporator of the CVD system, inert gas is introduced, the temperature of the reaction chamber is gradually increased, the system pressure is adjusted, and the reaction is carried out to obtain phosphorus and nitrogen co-doped three-dimensional graphene; then, a controllable laser system is used to irradiate the phosphorus and nitrogen co-doped three-dimensional graphene to obtain a three-dimensional graphene material with dual defects.

2. The method for preparing three-dimensional graphene with dual atomic-level defects according to claim 1, characterized in that: The pretreatment carbonization temperature described in step (1) is 400–800°C; The pretreatment carbonization time in step (1) is 0.5 to 4 hours; The flow rate of styrene mentioned in step (2) is 50-100 sccm; The flow rate of chlorine gas mentioned in step (2) is 20-60 sccm; The flow rate ratio of styrene to chlorine in step (2) is 0.5 to 4:1; The temperature for the chemical vapor deposition process described in step (2) is 100–1200 °C; The chemical vapor deposition process described in step (2) takes 0.1 to 9 hours. The temperature for the further processing described in step (2) is 50–500°C; The further processing time described in step (2) is 0.1 to 2 hours; The temperature of the reaction chamber mentioned in step (3) is 200–1000°C; The system pressure mentioned in step (3) is 10- 1 ~10- 4 Torr; The reaction time described in step (3) is 0.5 to 4 hours; The amount of liquid diethylphosphonamide used in step (3) is calculated based on 5-20 mL of liquid diethylphosphonamide per 100 mg of three-dimensional graphene sample; The power density of the laser irradiation in step (3) is 1–8 W / cm². 2 ; The laser irradiation time mentioned in step (3) is 5 to 20 minutes.

3. The method for preparing three-dimensional graphene with dual atomic-level defects according to claim 2, characterized in that: The pretreatment carbonization temperature described in step (1) is 600℃; The pretreatment carbonization time mentioned in step (1) is 2 hours; The temperature for the chemical vapor deposition process described in step (2) is 400–1000 °C; The chemical vapor deposition process described in step (2) takes 1 to 6 hours. The further processing temperature described in step (2) is 300°C; The further processing described in step (2) takes 1 hour; The temperature of the reaction chamber described in step (3) is 600℃; The system pressure mentioned in step (3) is 10- 2 Torr; The reaction time described in step (3) is 2 hours; The amount of liquid diethylphosphonamide used in step (3) is calculated based on 10 mL of liquid diethylphosphonamide per 100 mg of three-dimensional graphene sample; The power density of the laser irradiation mentioned in step (3) is 5 W / cm². 2 ; The laser irradiation time mentioned in step (3) is 10 minutes.

4. The method for preparing three-dimensional graphene with dual atomic-level defects according to claim 1, characterized in that: The biomass mentioned in step (1) is plant-based biomass; The vacuum environment mentioned in step (1) is a quartz tube that has been evacuated; The inert atmosphere mentioned in step (1) is argon; The vacuum environment mentioned in step (2) is a quartz tube that has been evacuated; Argon is used as the carrier gas for the styrene described in step (2); The inert gas mentioned in step (3) is argon.

5. The method for preparing three-dimensional graphene with dual atomic-level defects according to claim 1, characterized in that: The pressure of the vacuum environment described in step (1) is 5–20 mTorr; The flow rate of the inert atmosphere mentioned in step (1) is 40-80 sccm; The pressure of the vacuum environment described in step (2) is 5–20 mTorr; The flow rate of the inert gas mentioned in step (3) is 0 to 50 sccm, excluding the endpoint value of 0.

6. The method for preparing three-dimensional graphene with dual atomic-level defects according to claim 1, characterized in that: The heating rate of the chemical vapor deposition process described in step (2) is 0.1–20 °C / min. -1 ; The preparation conditions for the low-temperature plasma described in step (2) are as follows: the cavity pressure is 10- 2 ~10- 6 The ratio of Torr, hydrogen and nitrogen is 1:3 to 1:5, the total gas flow rate is 50 to 200 sccm, the excitation radio frequency is 100 to 300 W, and the temperature range is 50 to 500 °C. The temperature of the evaporator mentioned in step (3) is 40 to 100°C.

7. A three-dimensional graphene guided and regulated by dual atomic-level defects, characterized in that: It is obtained by the preparation method according to any one of claims 1 to 6.

8. A potassium-ion hybrid capacitor, characterized in that: It includes a positive electrode, a negative electrode, a separator, and an electrolyte; the negative electrode is made of three-dimensional graphene with dual atomic-level defects as described in claim 7; the positive electrode is made of three-dimensional graphene with dual atomic-level defects as described in claim 7 that has been thoroughly activated by KOH solution.

9. The potassium-ion hybrid capacitor according to claim 8, characterized in that: The electrolyte is a KFSI solution with a KFSI concentration of 1M, obtained by mixing diethyl carbonate and ethylene carbonate in a volume ratio of 1:

1. The diaphragm is made of glass microfiber.

10. The application of the three-dimensional graphene with dual atomic-level defects as described in claim 7, and the potassium-ion hybrid capacitor device as described in claim 8 or 9, in the field of electrochemical energy storage technology.

Citation Information

Patent Citations

  • Method for preparing nitrogen and phosphorus codoped porous graphene material

    CN103570011A

  • Preparation method of nitrogen, sulfur, and phosphor doped graphene sheet

    CN104828811A